The two-sided spectacle at the border: Frontex, NGOs and the theatres of sovereignty - Franko, Katja (Theoretical criminology, 2021)
The Southern Mediterranean border has in the past decade become one of the most deeply contested political spaces in Europe and has been described as a site of the border spectacle. Drawing on textual and visual analysis of Twitter messages by two of the most prominent actors in the field, the European Border and Coast Guard Agency, Frontex, and the humanitarian and medical NGO Médecins Sans Frontières, the article examines the split nature of the Mediterranean border which is, among others, visible in radically different narratives about migrants’ journeys, border deaths and living conditions. The findings challenge previous scholarship about convergence of humanitarianism and policing. The two actors are waging a fierce media battle for moral authority, where they use widely diverging strategies of claiming authority, each of which carries a particular set of ethical dilemmas.